2014
DOI: 10.1186/1476-511x-13-21
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E polymorphism is associated with lower extremity deep venous thrombosis: color-flow Doppler ultrasound evaluation

Abstract: IntroductionApolipoprotein E (apoE) is a member of apolipoprotein family, and its gene polymorphisms seem to have some impact among patients with cardiovascular disease. However, its role in the lower extremity deep venous thrombosis (LEDVT) has not been well studied. The objective of this study was to investigate the potential association between APOE gene polymorphisms and LEDVT.Materials and methodsA hospital-based case–control study was conducted in 300 patients with LEDVT by color-flow Doppler ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
4
21
1
1
Order By: Relevance
“…We did not find a significant association between Triglycerides plasma level and the risk of VTE, also the two studies of Kawasaki et al [11], Inge Van Schouwenburg et al [12], Everett [14] and Zamani have confirmed our finding [15][16][17][18][19][20][21][22][23][24][25][26][27][28], however, Carine Doggen et al [13], Amparo Vaya et al [6], Joel Ray et al [28] and Anders Holst [7] found a significant higher levels in patients.…”
Section: Patients (Mean ± Et) Controls (Mean ± Et) P Valuesupporting
confidence: 86%
See 2 more Smart Citations
“…We did not find a significant association between Triglycerides plasma level and the risk of VTE, also the two studies of Kawasaki et al [11], Inge Van Schouwenburg et al [12], Everett [14] and Zamani have confirmed our finding [15][16][17][18][19][20][21][22][23][24][25][26][27][28], however, Carine Doggen et al [13], Amparo Vaya et al [6], Joel Ray et al [28] and Anders Holst [7] found a significant higher levels in patients.…”
Section: Patients (Mean ± Et) Controls (Mean ± Et) P Valuesupporting
confidence: 86%
“…The difference in the Apo B/Apo A1 ratio between VTE patients and controls was statistically stronger, our results are consistent with Hiroshi Deguchi et al [19] but Amparo Vaya [6] show that Apo B/Apo A1 ratio is not a risk factor for venous thrombosembolism. We did not observe a significant difference in Apo E levels between patients and controls, and the few studies Jose Diaz [29] et al and Shuang Li Zhue [26] addressing this issue have failed to demonstrate a link between Apo E and VTE. When dichotomized into higher or lower than 0.91 mmol/l HDL-C groups, we found a significant association between HDL-C≤0.91 mmol/l in patients groups, this finding is confirmed by the Spanish study of Garcia Raso et al [27] but in contrast with him when we regard LDL-C above 4.66 mmol/L.…”
Section: Patients (Mean ± Et) Controls (Mean ± Et) P Valuecontrasting
confidence: 75%
See 1 more Smart Citation
“…ApoE can transport cholesterol and regulate lipid metabolism, and has become the focal point of recent studies (Al Harthi et al, 2014;Berkinbayev et al, 2014;Zurnić et al, 2014). In recent years, as the development of molecular biology and genetic engineering technologies has progressed, studies have demonstrated a close association between the ApoE gene polymorphism and serum lipid levels (Shin et al, 2014;Yin et al, 2014;Zhu et al, 2014). It has also been found that dietary factors had some impact on blood lipids, and that this effect could be modified by receptor lipoprotein metabolism (Petkeviciene et al, 2012;Rudkowska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CBF is lower in APOE ε4 carriers regardless of AD diagnosis (Kim et al 2013; Thambisetti et al 2010). In addition, APOE ε4 variant has been linked to venous thrombosis and flow abnormalities in lower extremities (Zhu et al 2014), although at the time of this writing, its effect on cerebral out-flow is not known.…”
Section: Introductionmentioning
confidence: 99%